Studi Kelayakan Pendirian Industri Kecil Pakan Ikan di Calingcing-Cianjur - Syamsu Darman; Fransiska R Zakaria; Tjahja Muhandri (Institut Pertanian Bogor, 2015)
Problems about high price of fish pellets could overcome by producing fish pellets with local ingredients. The objectives of this study were: (1) to analyze the feasibility of small fish pellets industry establishment in Calincing, Cianjur. Aspect of potential market, marketing, human resources, management technique, and production technology are analyzed descriptively; (2) Analyze financial feasibility aspect (NPV orNet Present Value, IRR or Internal Rate of Return, net B/C or Benefit/Cost, and PBP or Payback Periode). Ingredients of pellets which used for Nila Tilapia (Oreochromis sp.) had according to standard formula of BBAPT Sempur, Bogor. The composition were 20 kg of local fish meal, 28 kg soybean meal, 33 kg rice bran, 10 kg palm karnel meal, 2 kg of fish oil, 3 kg tapioca flour, 1 kg vegetable oil, 2 kg of top mix vitamin and 1 kg of mineral. The process of fish pellets production as follows: (1) receipts and storage of ingredients, (2) sorting, (3) screening, (4) weighing and formulation, (5) mixing, (6) hot steaming the ingredients, (7) pelleting, (8) drying; and (9) packing. The potential demand for Tilapia fish pellets in Cianjur were 149,321.28 tons per year and 25,704.80 kg per year in Ciranjang region. The investment cost for the establishment of fish pellets industry which production capacity of 1 ton per day or 300 tons per year was Rp1,755,800,000. Value cost for fish pellets production per kg was Rp5.764 with selling price was Rp6.800/kg, it got average margin as Rp693/kg. Feasibility criteria value showed that NPV was Rp452.852.260,073 at a discount rate of 14% per year (decent), IRR was 25,04% (decent), Net B/C was 1,45 (decent), and PBP was 3,09 or 3 years, 33 days (worthy).